2000
DOI: 10.1073/pnas.97.4.1891
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid acts as an inhibitory transmitter in the hypothalamus to inhibit stimulated luteinizing hormone-releasing hormone release by scavenging nitric oxide

Abstract: Because ascorbic acid (AA) is concentrated in synaptic vesicles containing glutamic acid, we hypothesized that AA might act as a neurotransmitter. Because AA is an antioxidant, it might therefore inhibit nitric oxidergic (NOergic) activation of luteinizing hormonereleasing hormone (LH-RH) release from medial basal hypothalamic explants by chemically reducing NO. Cell membrane depolarization induced by increased potassium concentration [K ؉ ] increased medium concentrations of both AA and LH-RH. An inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 46 publications
2
44
2
Order By: Relevance
“…The AA concentration measured in the AP in the present study was 300 M, an extremely high value that is in agreement with an earlier study (7) and is greater than the concentration found in the hypothalamus (21). Incubation of APs with medium containing high [K ϩ ] resulted in increased release of AA into the medium by a factor of 3 without altering tissue concentration, but the release was not dose-dependent.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The AA concentration measured in the AP in the present study was 300 M, an extremely high value that is in agreement with an earlier study (7) and is greater than the concentration found in the hypothalamus (21). Incubation of APs with medium containing high [K ϩ ] resulted in increased release of AA into the medium by a factor of 3 without altering tissue concentration, but the release was not dose-dependent.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to the stimulatory effect of AA on gonadotropin secretion from APs, AA had no effect on basal LHRH release from medial basal hypothalamic explants but significantly lowered NP or excitatory amino acid NMDA-stimulated LHRH release. NP or NMDA-induced LHRH release is mediated by NO, and AA acts as an inhibitory transmitter in the hypothalamus to inhibit stimulated LHRH release by scavenging NO (21). Our current data suggest that AA has opposite effects at the hypothalamic and pituitary levels, inhibiting LHRH release in the medial basal hypothalamus and inducing gonadotropin release from the anterior pituitary.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Similar ameliorating effects of AA against EOF were reported in transported pigs (Adenkola & Ayo 2009;Asala et al 2011) and goats (Minka & Ayo 2010b) under extreme thermal environment. The mechanism by which AA protected the erythrocytes of the rabbits from haemolysis may be through the inhibitory role of AA on corticosterone (Karanth et al 2000;Balz 2003), and its detoxifying and scavenging effects on free radicals generated during transportation (Seibert et al 2001;Urban-Chmiel et al 2009;Minka & Ayo 2010a). Besides, AA has been demonstrated to reduce the capacity of O 2 consumption through tissue oxidative metabolism and decrease heat load by enhancing mechanism of thermoregulation via increasing heat loss (Kuth & Forbes 1993), which may also decrease the generation of free radicals and further reduce lipopeoxidation.…”
Section: Post-transportation Periodmentioning
confidence: 99%
“…Therefore, by affecting the thermoregulatory centre, the antioxidant vitamins apparently exerted ameliorating effects on the elevated CT in the transported quails. Furthermore, the fact that these vitamins are known to inhibit the release of cortisol [40,42], the chief fear hormone, may be involved in the mechanism of regulation of the body responses, aimed at maintaining homeostasis. In addition, VE and AA have been reported to reduce heat load in birds [12,14,16,21,43].…”
Section: Discussionmentioning
confidence: 99%